Capital adequacy regulation of financial conglomerates in the European Union - Y. Emilie Yoo (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2010)
Over the past few decades, changes in market conditions such as globalisation and deregulation of financial markets as well as product innovation and technical advancements have induced financial institutions to expand their business activities beyond their traditional boundaries and to engage in cross-sectoral operations. As combining different sectoral businesses offers opportunities for operational synergies and diversification benefits, financial groups comprising banks, insurance undertakings and/or investment firms, usually referred to as financial conglomerates, have rapidly emerged, providing a wide range of services and products in distinct financial sectors and oftentimes in different geographic locations. In the European Union (EU), financial conglomerates have become part of the biggest and most active financial market participants in recent years. Financial conglomerates generally pose new problems for financial authorities as they can raise new risks and exacerbate existing ones. In particular, their cross-sectoral business activities can involve prudentially substantial risks such as the risk of regulatory arbitrage and contagion risk arising from intra-group transactions. Moreover, the generally large size of financial conglomerates as well as the high complexity and interconnectedness of their corporate structures and risk exposures can entail substantial systemic risk and can therefore threaten the stability of the financial system as a whole. Until a few years ago, there was no supervisory framework in place which addressed a financial conglomerate in its entirety as a group. Instead, each group entity within a financial conglomerate was subject to the supervisory rules of its pertinent sector only. Such silo supervisory approach had the drawback of not taking account of risks which arise or aggravate at the group level. It also failed to consider how the risks from different business lines within the group interrelate with each other and affect the group as a whole. In order to address this lack of group-wide prudential supervision of financial conglomerates, the European legislator adopted the Financial Conglomerates Directive 2002/87/EC8 (`FCD') on 16 December 2002. The FCD was transposed into national law in the member states of the EU (`Member States') by 11 August 2004 for application to financial years beginning on 1 January 2005 and after. The FCD primarily aims at supplementing the existing sectoral directives to address the additional risks of concentration, contagion and complexity presented by financial conglomerates. It therefore provides for a supervisory framework which is applicable in addition to the sectoral supervision. Most importantly, the FCD has introduced additional capital requirements at the conglomerate level so as to prevent the multiple use of the same capital by different group entities. This paper seeks to examine to what extent the FCD provides for an adequate capital regulation of financial conglomerates in the EU while taking into account the underlying sectoral capital requirements and the inherent risks associated with financial conglomerates. In Part 1, the definition and the basic corporate models of financial conglomerates will be presented (I), followed by an illustration of the core motives behind the phenomenon of financial conglomeration (II) and an overview of the development of the supervision over financial conglomerates in the EU (III). Part 2 begins with a brief elaboration on the role of regulatory capital (I) and gives a general overview of the EU capital requirements applicable to banks and insurance undertakings respectively. A delineation of the commonalities and differences of the banking and the insurance capital requirements will be provided (II). It continues to further examine the need for a group-wide capital regulation of financial conglomerates and analyses the adequacy of the FCD capital requirements. In this context, the technical advice rendered by the Joint Committee on Financial Conglomerates (JCFC) as well as the currently ongoing legislative reforms at the EU level will be discussed (III). The paper finally closes with a conclusion and an outlook on remaining open issues (IV).
urn:nbn:de:hebis:30-76201
Keywords: 330